Faktor-Faktor yang Mempengaruhi Kejadian Asfiksia Neonatorum di RSUD DR Tengku Mansyur Kota Tanjung Balai Tahun 2023 - Etna Kartika Sari; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Rahmah Rahmah (PPNI UNIMMAN, 2025)
Asphyxia is a condition in which a baby has difficulty breathing spontaneously and regularly immediately after birth, so that it cannot obtain oxygen and remove carbon dioxide from its body. This condition occurs due to pathological changes caused by a lack of oxygen in the respiratory system, which can result in hypoxia and hypercapnia. Asphyxia can also be grouped into two types, namely primary asphyxia that occurs when a baby is born and secondary asphyxia that occurs some time after birth. This study aims to determine what factors influence the incidence of asphyxia at RSUD DR Tengku Mansyur Tanjungbalai City in 2023. The type of research is an analytical survey study with a cross-sectional design used to determine the relationship between maternal age, gestational age, parity, and amniotic fluid with the occurrence of neonatal asphyxia at RSUD DR Tengku Mansyur Tanjungbalai City in 2023. The research sample consisted of 25 people, who were selected using a sampling technique with the Total Sampling Technique. The results of the bivariate analysis using the Fisher's Exact Test showed a p-value of 0.344. Thus, it can be concluded that there is no statistically significant relationship between maternal age and the incidence of neonatal asphyxia at DR. Tengku Mansyur Regional Hospital, Tanjung Balai City, in 2023.